Cardiac arrest, chronic total occlusion, and occluded stent in a 16-year-old boy with Kawasaki disease: a case report. Issue 6 (4th November 2020) - Connolly, Michelle J; Khan, Sarosh; Li Kam Wa, Matthew E; Faircloth, Matthew E; Clapp, Brian
Abstract: Background: Kawasaki disease is the leading cause of premature coronary artery disease in developed countries. As such, patients may require revascularisation as children. However, there are no randomized data guiding treatment so this must be individualized. This case report describes the decision-making in a young patient requiring revascularization who had already suffered stent occlusion. Case summary: Our patient, a 16-year-old boy with Kawasaki disease, presented with cardiac arrest during exercise. Coronary angiography showed that a proximal left anterior descending artery stent implanted at the age of 8 years had occluded some time ago and his right coronary artery was also chronically occluded. He has discussed in several Heart Team meetings and with international colleagues and a consensus reached to revascularize him surgically. Discussion: It is vital that young patients with complex coronary disease are discussed in an extensive multidisciplinary setting to determine the most suitable means of treatment. The previously occluded stent was crucial in the individualized decision-making in this patient.